PROVIDING EFFECTIVE GENERAL CARE DURING THE DIFFERENTIATION PERIOD OF TRANSIENT CEREBROVASCULAR PATHOLOGIES (International journal of medical sciences, 2025)
Acute cerebrovascular accident is a very serious and severe cerebrovascular pathology. Based on the latest WHO data, the mortality rate for ischemic stroke is from 10% to 25%, for hemorrhagic stroke - from 45% to 60%. The main complications leading to death include: brain edema, pulmonary edema, various types of heart failure and heart failure. In other cases, the consequences may be irreversible or temporary and are manifested by regression of communication, speech, emotional and other higher functions. A significant deterioration is observed in the first three months after a cerebrovascular accident.